2022
DOI: 10.3389/fcell.2022.809922
|View full text |Cite
|
Sign up to set email alerts
|

Two Compact Cas9 Ortholog-Based Cytosine Base Editors Expand the DNA Targeting Scope and Applications In Vitro and In Vivo

Abstract: CRISPR/Cas9-based base editing tools enable precise genomic installation and hold great promise for gene therapy, whereas the big size of Cas9 nucleases and its reliability on specific protospacer adjacent motif (PAM) sequences as well as target site preferences restrict the extensive applications of base editing tools. Here, we generate two cytosine base editors (CBEs) by fusing cytidine deaminases with two compact codon-optimized Cas9 orthologs from Streptococcus_gordonii_str._Challis_substr._CH1 (ancSgo-BE4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…Indeed, the replacement of APOBEC1 with APOBEC3A (Y130F) significantly improved the performance of SsiCas9-mediated CBE in GC and non-GC targets (Figure 2). Combining with our recently reported findings, [48] these results indicated that engineering CBEs with APOBEC3A might be a universal strategy to improve the sequence-context bias. However, considering the relatively high indel rates induced by ancSsi-A3A-BE4, when sufficient targeting efficiency can be achieved using ancSsi-BE4, ancSsi-A3A-BE4 can serve as a strong backup tool for inducing targeted cytosine conversion.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Indeed, the replacement of APOBEC1 with APOBEC3A (Y130F) significantly improved the performance of SsiCas9-mediated CBE in GC and non-GC targets (Figure 2). Combining with our recently reported findings, [48] these results indicated that engineering CBEs with APOBEC3A might be a universal strategy to improve the sequence-context bias. However, considering the relatively high indel rates induced by ancSsi-A3A-BE4, when sufficient targeting efficiency can be achieved using ancSsi-BE4, ancSsi-A3A-BE4 can serve as a strong backup tool for inducing targeted cytosine conversion.…”
Section: Discussionsupporting
confidence: 87%
“…To broaden the usage of base editing with various PAM recognition capabilities, we selected SsiCas9, which is smaller than SpCas9 (1121 vs. 1368 residues, Figure S1A), has high cleavage activity at 37°C, and recognizes NNAAAA PAM sequence in in vitro biochemical assays (Figure S1B), as a potentially novel Cas9 protein from 79 Cas9 homologs library [ 34 ] for base editor engineering. Compared to the scaffold sequence of the gRNAs for SpCas9, 45.56% of the nucleotides were conserved with those of SsiCas9 (Figure S1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Base editing (BE) is a technique that directly converts one target genomic DNA base into another at a targeted locus without producing a double-stranded break. Combining cytosine or adenine deaminases with CRISPR-Cas9, a range of cytosine base editors (CBEs) and adenine base editors (ABEs) has been developed in recent years [ 66 , 67 , 68 ]. These varieties allow exact C-to-T or A-to-G base conversions without causing a DSB.…”
Section: The Crispr/cas Systemmentioning
confidence: 99%